2017
DOI: 10.1016/j.jclinepi.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Series: Pragmatic trials and real world evidence: Paper 3. Patient selection challenges and consequences

Abstract: This paper addresses challenges of identifying, enrolling, and retaining participants in a trial conducted within a routine care setting. All patients who are potential candidates for the treatments in routine clinical practice should be considered eligible for a pragmatic trial. To ensure generalizability, the recruited sample should have a similar distribution of the treatment effect modifiers as the target population. In practice, this can be best achieved by including-within the selected sites-all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 43 publications
0
53
0
1
Order By: Relevance
“…Exclusion of patients from trials matters only if the exclusion criteria are effect modifiers of treatment [27], meaning that the benefits or harms of treatment (or both) systematically vary in the included versus the excluded. This review found that trial evidence is typically derived from narrow populations which are usually selected to have higher risk of outcomes expected to be improved by treatment (e.g., by selective inclusion of patients at high cardiovascular risk) and usually selected to have lower risk of adverse effects (e.g., by selective exclusion of patients with co-morbidity, co-prescribing and frailty).…”
Section: Implications For Policy Practice and Researchmentioning
confidence: 99%
“…Exclusion of patients from trials matters only if the exclusion criteria are effect modifiers of treatment [27], meaning that the benefits or harms of treatment (or both) systematically vary in the included versus the excluded. This review found that trial evidence is typically derived from narrow populations which are usually selected to have higher risk of outcomes expected to be improved by treatment (e.g., by selective inclusion of patients at high cardiovascular risk) and usually selected to have lower risk of adverse effects (e.g., by selective exclusion of patients with co-morbidity, co-prescribing and frailty).…”
Section: Implications For Policy Practice and Researchmentioning
confidence: 99%
“…Whether the return of SLCO1B1 results is acted upon by providers and leads to improvement in patient outcomes remains unknown but will be addressed by the trial's outcomes. One risk of applying a pragmatic design to study a precision medicine intervention is that the broad eligibility criteria, a strength of PCTs, may dilute the effect of the intervention . If so, examining the reasons the providers and patients did not act on the information will be critical for interpreting the trial's results.…”
Section: Discussionmentioning
confidence: 99%
“…Instruments to assess the outcome should be sufficiently accurate (ie, valid, reliable, and responsive) and feasible in terms of costs and complexity [41e43]. Deviations from routine clinical practice should be minimized, also to promote the acceptability of measurements to patients and care providers who participate in a study [7,[44][45][46]. It may be beneficial for decision making to apply a predefined cutoff value for continuous outcome measures in a pragmatic trial when resulting categorical outcomes have a clearer meaning for interpretation of trial results at patient level (ie, the probability of recovery).…”
Section: Measuring Outcomesmentioning
confidence: 99%